Effect of feeding fermentable synbiotics (Lactobacillus rhamnosus NCDC 298 and fructo-oligosaccharide) to Jersey crossbred calves up to 3 months of age - RAI, S; MANDAL, S; BEHERA, R; SAHU, J; DUTTA, T K; JAS, R; CHATTERJEE, A; MANDAL, D K; KARUNAKARAN, M; GHOSH, M K (The Indian Journal of Animal Sciences, 2020)
The synbiotic combination of L. rhamnosus NCDC 298 and fructo-oligosaccharide (FOS) is known to be effective against diarrhoea by preventing the adhesion of pathogens to the gutt, hereby, preventing infection and pathology. Such synergistic effect of the combination has emerged as a favourable alternative to antibiotic use against diseases and growth promoters in the livestock industry. The present study assessed the health and growth performance of the calves supplemented fermentable synbiotic fortified milk from 4 to 90 days and observed its performance till 120th day of age. Body temperature and passive immunity (IgG) were significantly better in calves fed synbiotics with notable increase in body weight and heart girth post synbiotic feeding period. These calves had increased dry matter intake per animal/day when compared to the control animals. The populations of Lactobacillus sp. elevated with decreased pathogenic bacteria (Coliform) in faeces on feeding synbiotics and it continued even after 90 days of age indicating colonization of beneficial bacteria. Therefore, feeding of fermentable synbiotics had observable beneficial effects on health, immunity and growth of the Jersey crossbred calves. The findings encourage further verification of fermentable synbiotics fortified milk as a potential growth promoter to young dairy calves.